The effect of a carbohydrate and protein supplement in resistance exercise on performance, hormonal response, and muscle damage - Baty, J. J.; Hwang, H.; Ding, Z.; Bernard, J. R.; Wang, B.; Kwon, B.; Ivy, J. L. (The Journal of Strength and Conditioning Research, 2007)
The purpose of this study was to determine whether resistance exercise performance and postexercise muscle damage were altered when consuming a carbohydrate and protein beverage (CHO-PRO; 6.2% and 1.5% concentrations). Thirty-four male subjects (age: 21.5 +/- 1.7 years; height: 177.3 +/- 1.1 cm; weight: 77.2 +/- 2.2 kg) completed 3 sets of 8 repetitions at their 8 repetition maximum to volitional fatigue. The exercise order consisted of the high pull, leg curl, standing overhead press, leg extension, lat pull-down, leg press, and bench press. In a double-blind, posttest-only control group design, subjects consumed 355 ml of either CHO-PRO or placebo (electrolyte and artificial sweetener beverage) 30 minutes prior to exercise, 177 ml immediately prior to exercise, 177 ml halfway through the exercise bout, and 355 ml immediately following the exercise bout. There were no significant differences between groups relative to exercise performance. Cortisol was significantly elevated in the placebo group compared to the CHO-PRO group at 24 hours postexercise. Insulin was significantly elevated immediately pre-exercise, after the fourth lift, immediately postexercise, 1 hour, and 6 hours postexercise in CHO-PRO compared to the placebo group. Myoglobin levels in the placebo group approached significance halfway through the exercise bout and at 1 hour postexercise (p = 0.06 and 0.07, respectively) and were significantly elevated at 6 hours postexercise compared to the CHO-PRO group. Creatine kinase levels were significantly elevated in the placebo group at 24 hours postexercise compared to the CHO-PRO group. The CHO-PRO supplement did not improve performance during a resistance exercise bout, but appeared to reduce muscle damage, as evidenced by the responses of both myoglobin and creatine kinase. These results suggest the use of a CHO-PRO supplement during resistance training to reduce muscle damage and soreness.